Comparison of treatment outcome between glucocorticoids and non-steroidal anti-inflammatory drugs in subacute thyroiditis patients—a systematic review and meta-analysis - Yuan, Anqi; Wu, Jialu; Huang, Hui (Frontiers in Endocrinology, 2024)
Importance Subacute thyroiditis (SAT) is a self-limiting and inflammatory thyroid disease. Although SAT usually improves on its own within weeks, it needs treatment when patients have pain, fever, and symptoms of thyrotoxicosis. Therapeutic drugs mainly include non-steroidal anti-inflammatory drugs (NSAIDs) and glucocorticoids. Currently, there is no systematic review or meta-analysis of the comparison of outcomes between NSAIDs and glucocorticoids for the treatment of SAT. Objectives To conduct a systematic review and meta-analysis on the outcomes in subacute thyroiditis patients treated with glucocorticoids or NSAIDs. Data sources Using the four electronic databases, including PubMed, Embase, Cochrane Library, Wanfang database and Web of Science. All publications until 21 June 2023 were searched. The reference lists of all selected articles were independently screened to identify additional studies left out in the initial search. Study selection The literature comparing outcomes between glucocorticoids and non-steroidal anti-inflammatory drugs for patients with subacute thyroiditis will be included. Data extraction and synthesis Two independent investigators (Anqi Yuan and Jialu Wu) extracted the data following Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines (PRISMA) and then evaluated the quality of the eligible studies with the Newcastle-Ottawa Scale. Fixed-effects models for the meta-analyses were applied. Heterogeneity was assessed with the chi-squared (x²) test (Cochran’s Q) and inconsistency index (I²). The robustness of the results was tested with the sensitivity analyses. The bias of publication was assessed with the Harbord test. Main outcomes and measures The incidence of permanent hypothyroidism in SAT patients treated with corticosteroids or NSAIDs. Results Our study included a total of ten comparative cohort studies with 1337 participants. We found that the incidence of developing permanent hypothyroidism in the SAT patients who received glucocorticoids treatment was significantly lower than those who received NSAIDs treatment. (OR, 0.56; 95% CI, 0.36–0.88; P = 0.01). The risk of permanent hypothyroidism in patients who received prednisone at an average initial dose < 40 mg/d was significantly lower than that in patients who received NSAIDs (OR, 0.37; 95% CI, 0.14–0.94; P = 0.04). There was no significant difference in the occurrence of permanent hypothyroidism between SAT patients who received an average initial dose ≥ 40 mg/d of prednisone and those who received only NSAIDs (OR, 0.7; 95% CI, 0.14–3.53; P = 0.67). In addition, the recurrence rate was observably higher in those receiving glucocorticoids than in those receiving NSAIDs (OR, 1.98; 95% CI, 1.12–3.5; p = 0.02). The recurrence rate was significantly higher in patients with an average initial prednisone dose of < 40 mg/d than in the NSAIDs group. There was no significant difference in the recurrence rate between patients in the mean initial prednisone dose ≥ 40 mg/d group and those in the NSAIDs group. Conclusions and relevance In this meta-analysis, we compared the treatment outcomes of SAT patients between glucocorticoids and NSAIDs. Our results indicated that glucocorticoid treatment was associated with a lower incidence of permanent hypothyroidism than NSAID treatment. Patients treated with NSAIDs might have a lower recurrence rate. This finding might help to understand the outcome of the disease when choosing different drugs and help physicians to make appropriate decisions. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023427332.